A Comparative Analytical Study of Gold Credit Sale and Gold Pawn (Rahn) Based on Classical Fiqh, DSN-MUI Perspectives, and Aaoifi Standards - Edi Suwanto; Dwi Sanday; Mujibu Da’wat (STAI Publisistik Thawalib Jakarta, 2026)
The research problem arises from the differences in the concept of ribawi ‘illah, DSN-MUI fatwas, and AAOIFI standards in credit-based and digital gold transactions, which create uncertainty in Islamic legal rulings. The objective of this study is to analyze the differences between classical fiqh, DSN-MUI, and AAOIFI regarding credit gold and rahn, and to formulate an adaptive Sharia decision map for physical and digital gold transactions based on maqasid al-shari‘ah. This qualitative normative-comparative research employs literature review, documentation, ‘illah analysis, and maqasid al-shari‘ah to compare classical fiqh, DSN-MUI, and AAOIFI and reconstruct the legal framework of digital and physical gold transactions. The findings indicate significant differences in determining the ribawi‘illah of gold and the legal status of credit and digital gold transactions. Classical fiqh and AAOIFI maintain that gold remains a ribawi asset, thus prohibiting credit-based sales, whereas DSN-MUI adopts a contextual approach that allows transactions under conditions of qabd and the absence of gharar. In gold collateral (rahn), all perspectives agree on ownership principles but differ in the level of regulatory strictness. Digital gold transactions are considered valid when backed by physical assets and audited reserves, whereas unallocated gold, CFDs, and leverage trading are deemed invalid due to high speculation, gharar, and lack of Sharia compliance. In conclusion, ownership certainty and transaction transparency are the key determinants of Sharia validity in modern gold credit and digital transactions. The significance of this study lies in strengthening Sharia legal certainty, supporting the digital gold industry, and assisting regulators in developing adaptive Islamic financial policies.